Effect Aerobic Exercise On Cardiorespiratory Fitness In Athlete - Amanati, Suci; Boki Jaleha; Maya Triyanita (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: Cardiorespiratory fitness or fitness is one of the endogenous factors that can affect athlete performance, this is because good cardiorespiratory fitness shows good endurance capabilities. Cardiorespiratory fitness can be improved one of them with aerobic exercise. Aerobic exercise done regularly is expected to increase the level of cardiorespiratory fitness in athletes. Objective: This study aims to determine the effectiveness of exercise with aerobic exercise on cardiorespiratory fitness that is applied regularly by FC Bintang Utama Semarang athletes at GOR Manunggal Jati Semarang City in preparation for the Mayor Cup competition. Methods: The research method uses an experimental design on athletes at FC Bintang Utama Semarang with the number of respondents involved as many as 30 athletes with an age range of 14-17 years. Results: Cardiorespiratory fitness results are measured using the bleep test. The bleep test evaluation was carried out on the first day and the last day of the study. Analysis of the results of the effectiveness of aerobic exercise on cardiorespiratory fitness with the results of statistical tests using the paired T Test obtained the final result of 0.00 where this value is smaller than 0.05 which indicates an increase in cardiorespiratory fitness level. Conclusion: The conclusion of this study is that aerobic exercise done regularly can improve cardiorespiratory fitness.